2017
DOI: 10.1097/mpa.0000000000000783
|View full text |Cite
|
Sign up to set email alerts
|

The Changing Epidemiology of Acute Pancreatitis Hospitalizations

Abstract: Objectives The epidemiological trends contributing to increasing acute pancreatitis (AP) hospitalizations remain unknown. We sought to analyze etiological factors and outcomes of increasing AP-hospitalizations. Methods Utilizing the Nationwide Inpatient Sample, retrospective analyses of adult (≥18 years) inpatient admissions with a primary diagnosis of AP (total N: 2,016,045) were performed. Patient hospitalizations from 2009–2012 were compared to those from 2002–2005. Results Compared to 2002–2005, there … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
110
1
5

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(119 citation statements)
references
References 24 publications
3
110
1
5
Order By: Relevance
“…Non-U.S. studies, particularly European ones, also showed similar increases in the incidence over time [22]. Gallstone pancreatitis seems to universally have the most significant contribution to the rise in the number of cases [9,11,22,23]. However, alcohol appears to be the cause that remained steady over time across different countries.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Non-U.S. studies, particularly European ones, also showed similar increases in the incidence over time [22]. Gallstone pancreatitis seems to universally have the most significant contribution to the rise in the number of cases [9,11,22,23]. However, alcohol appears to be the cause that remained steady over time across different countries.…”
Section: Discussionmentioning
confidence: 79%
“…Expectedly, the number of annual hospitalizations at our center in Riyadh was almost double the figures shown in Al-Karawi et al ' s [2] study in 2001 (107 admissions to our center in 3 years; 35.7/year). This could be due to the change in the diagnostic criteria used to label patients with AP [21], easier access to health care services and more liberal laboratory testing [9], or, an actual increase in the incidence due to the rising prevalence of risk factors (obesity, gallstones, hypertriglyceridemia, etc.) [9].…”
Section: Discussionmentioning
confidence: 99%
“…Reduced pancreatic microcirculation in severe pancreatitis induces hypoxia of the pancreatic tissue and consequently the inflammatory cascade and tissue necrosis. Pancreatic tissue necrosis is not homogeneous, and toxic mediators that further compromise pancreatic microcirculation are released [3,6,8]. Interestingly, both alcohol and cigarette smoke seem to selectively impair hemoglobin oxygen saturation in the pancreas and may thereby additionally provoke pancreatic hypoxia [9,10].…”
Section: Pancreatic Microcirculation - Capillary Blood Flowmentioning
confidence: 99%
“…While most patients develop mild disease, up to 20% develop moderate to severe pancreatitis with pancreatic necrosis and/or multi-organ failure [1,2]. The incidence has been rising in recent years, and especially the severe forms are a major clinical and financial health care burden [3]. The most common etiologic factors are gallstones and alcohol, followed by ischemia, hyperlipidemia, hypercalcemia, and hereditary factors.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence varies from 5 to 30 cases per 100,000 individuals [2]. There is evidence for an increase in the incidence of AP over the last decade, but these data need to be interpreted with caution, since acute bouts of chronic pancreatitis are often counted as AP in registries and insurance records [3]. …”
Section: Introductionmentioning
confidence: 99%